MAKASSAR CULTURAL VALUES IN THE TEXTS OF SELAYAR BATIKS FOLK SONGS - Rengko HR, Sumarlin; Milda, Milda; Hermansyah, Sam (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
One of the oral traditions that has developed to date in the Selayar Islands Regency is battki. Battik-battik belongs to the categories of folk songs. Battik-battik comes from the word ambatti which means to squeeze. The musical instrument used is the harp, therefore it is called battik- battik. Battik-battik is sung by men and women alternately on stage without using text, meaning this song is sung spontaneously. In the batti-batti folk song, there are cultural values sung by the singer, namely the culture of tabe, sipakatu and si usingnga'. So that in this study the authors used multi-disciplines, namely anthropolinguistics with the aim of exploring these cultures hidden in the text or song lyrics that are sung. Anthropolinguistics is a study that discuss the relationship or connection between culture and language. in anthropolinguistics studies examiners more how languages is used US a tools for social action. This research method uses qualitative research methods to explain a phenomenon in depth and is carried out by collecting data as deeply as possible.